Hormonal and dietary factors in acne vulgaris versus controls. Issue 1 (1st January 2018) - Stewart, Thomas Jonathan; Bazergy, Carl
ABSTRACT: Background : Acne vulgaris is an inflammatory skin disorder with not as yet fully understood pathogenesis. In this controlled study, we assessed acne vulgaris patients for several possible pathogenic factors such as vitamin D deficiency, vegan diet, increased body mass index (BMI) and positive anti-transglutaminase antibody.Methods : We screened 10 years of records at a family medicine clinic for patients diagnosed with acne vulgaris. In eligible subjects, we collected data regarding 25-hydroxylvitamin D levels, BMI, dietary preference and serum IgA tissue transglutaminase levels. Controls were age- (+/− 12 months) and sex-matched patients seen during the study period without a diagnosis of acne vulgaris.Results : 453 patients were given a diagnosis of acne vulgaris during the study period. Compared with controls, we found significant associations between vitamin D deficiency (<50nmol/L), and/or positive transglutaminase antibody level (>4.0U/mL) and a diagnosis of acne vulgaris.Conclusions : Our study adds important information to the current body of literature in pursuit of elucidating the pathogenesis of this complex multifactorial disease.